Psychometric characteristics, cross-cultural adaptation and validation of the Slovenian version of the Victorian Institute of Sports Assessments for Gluteal tendinopathy questionnaire (VISA-G) - Roškar, Samo (Zdravstveno varstvo, 2023)
Introduction: Greater trochanteric pain syndrome (GTPS) denotes several disorders around the lateral aspect of the hip. GTPS may develop in native hips as well as after total hip arthroplasty (THA). It is estimated that 5-12% of patients suffer from GTPS after primary THA. Despite the prevalence of GTPS, it is hard to diagnose and manage it properly. The VISA-G questionnaire was developed as a patient-reported outcome measurement tool for evaluation of GTPS. The aims of the present study were to evaluate the reliability of the VISA-G Slovenian and its construct and criterion validity. Methods: After the finalization of the VISA-G Slovenian translation procedure, 59 patients with a painful trochanteric region planned for THA filled in the VISA-G Slovenian at the hospital on two occasions 5-7 days apart. On the first occasion, each patient also filled in the EQ-5D-5L questionnaire and the Harris Hip Score (HHS) was completed by the physiotherapist. Results: The VISA-G Slovenian was found to have a test-retest reliability of ICC 0.977; 95% CI 0.96; 0.986. Internal consistency was assessed with Cronbach’s alpha 0.79. The statistically significant, but low, correlation between the HHS and VISA-G (r=0.48) was obtained. Concurrent validity of the VISA-G with the EQ-5D-5L showed moderate to strong correlations in Mobility, Self-Care, Usual Activities, Pain, EQ-5D-5L Index and EQ VAS, but low correlation in the Anxiety subscale. No floor and ceiling effect were obtained. Conclusions: The VISA-G Slovenian has excellent psychometric properties needed to measure gluteal tendinopathy-related disability of patients in Slovenia. Thus, we recommend using the questionnaire for measuring trochanteric hip pain.
Keywords: bolečinski sindrom v predelu velikega trohantra; greater trochanteric pain syndrome; hips; izidi; kolki; outcomes; psihometrične značilnosti; psychometric properties; Slovenia; Slovenija; tendinopathy; tendinopatija; zanesljivos